Pengenalan Strategi Branding Produk Lokal Pada Usaha Mikro Kecil Dan Menengah (Umkm) Melalui Media Digital Di Desa Sri Kuncoro - Nopiah, Ririn; Rusdi, Muhammad; Sitorus, Antoni (UNIB Press, 2025)
Micro, Small, and Medium Enterprises (MSMEs) based on local resources have great potential in driving village economic growth. However, low product branding capacity is often a major obstacle in increasing MSME competitiveness in the wider market. This community service activity aims to introduce basic strategies for local product branding to MSMEs in Sri Kuncoro Village, Central Bengkulu Regency, by utilizing digital media as an effective and affordable promotional tool. Through socialization, participants were introduced to the importance of brand identity, product storytelling techniques, basic principles of packaging design, and the use of digital platforms such as WhatsApp Business, Instagram, and local marketplaces. It is hoped that this activity will increase MSMEs' understanding of the importance of product image, expand market reach, and encourage the growth of businesses based on local potential.